2008
DOI: 10.1007/s10493-008-9218-y
|View full text |Cite
|
Sign up to set email alerts
|

Development and reproductive capacity of the predatory mite Parasitus consanguineus (Acari: Parasitidae) reared on the larval stages of Megaselia halterata and Lycoriella ingenua

Abstract: Development and reproduction of the predatory mite Parasitus consanguineus Oudemans et Voigts (Acari: Parasitidae) reared on a diet of first and second instars of Megaselia halterata (Diptera: Phoridae) or Lycoriella ingenua (Diptera: Sciaridae) were studied. Mites were allowed to feed on these diets until death. The developmental time of immature stages of P. consanguineus was significantly longer when reared on L. ingenua than on M. halterata larvae (8.3 vs. 7.9 days, respectively). Survival to adulthood of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 13 publications
2
7
1
1
Order By: Relevance
“…The biology of Parasitus consanguineus Oudemans & Voigts fed with first and second instars of Megaselia halterata (Diptera: Phoridae) or Lycoriella ingenua (Diptera: Sciaridae) was studied by Szlendak and Lewandowski also at 21 °C. In that study, the mites were apparently maintained in groups of 100 individuals.…”
Section: Discussionsupporting
confidence: 52%
“…The biology of Parasitus consanguineus Oudemans & Voigts fed with first and second instars of Megaselia halterata (Diptera: Phoridae) or Lycoriella ingenua (Diptera: Sciaridae) was studied by Szlendak and Lewandowski also at 21 °C. In that study, the mites were apparently maintained in groups of 100 individuals.…”
Section: Discussionsupporting
confidence: 52%
“…The only available data are for R. consanguineus (Szlendak and Lewandowski 2009). This publication does not contain r m values; the authors report fecundity, longevity and duration of oviposition period for the species reared on phorid and sciarid larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Larvae of L. ingenua and M. halterata were also accepted as a prey by R. consanguineus . Studies showed that R. consanguineus can complete development on a diet of larvae of M. halterata and L. ingenua , which indicates that it has potential as a predatory mite for controlling both these pest species (Szlendak and Lewandowski 2009). The studies mentioned suggest that predatory mites in mushroom houses can be considered as natural enemies of mushroom pests, and that some of them may replace chemicals in mushroom pest control.…”
Section: Introductionmentioning
confidence: 99%
“…For Parasitus consanguineus Oudemans & Voigts fed with first and second instars of Megaselia halterata (Diptera: Phoridae) or Lycoriella ingenua (Diptera: Sciaridae), again at 21 o C, Szlendak and Lewandowski (2009) reported slightly longer or shorter durations of different developmental stages and longevity, but much lower fecundity (12.3 and 17.8 eggs/female on those respective prey) than found in this study for mites paired continuously, and on all diets.…”
Section: Discussioncontrasting
confidence: 45%